Gerenciamento integrado de projetos como suporte ao ecossistema de saúde para entrega de serviços aos pacientes - Geraidine, Ricardo Santos (2024)
The healthcare sector is considered of high complexity due to the interdependence between its various agents so that the healthcare service can be provided to the patient and the population. Some challenges in the sector are economic imbalance, increasing capacity of the growing demand, increased chronic diseases due to the aging of the population, insufficient labor and, at the same time, meeting the expectations and need of patients. Agents that make up the healthcare ecosystem often act in a fragmented way with dysfunctional processes, unintegrated information systems and low adaptation to the rapid transformations that the sector requires. Thus, the purpose of this dissertation is to propose the conceptual guidance model of integrated project management to support the healthcare ecosystem to provide services to patient's journey. To this end, the research was implemented in two stages, following a qualitative approach. The first stage came from the execution of a Systematic Literature Review (SLR) composed of 2,575 articles obtained through the Scopus, Web of Science and PubMed databases, and 249 articles were selected to understand the theoretical assumptions and management gaps of projects in the healthcare sector. SLR's results have shown that there are several project management practices applied to the healthcare sector, but they focus on solving only part of the problem. In this sense, we identify the opportunity to connect this knowledge and propose a model that serves as a guidance guide for healthcare managers to manage their projects in an integrated way to deliver services on the patient's journey. The second stage of the research included semi-structured interviews and focus groups to incorporate the experience of practitioners to refine the orientative conceptual model. There were 12 individual interviews and three focal group sessions. The results of this phase allowed bring to the model developed in the first phase closer to the perceptions and experience of practitioners. Other results are the identification of five main barriers and five main facilitators for the implementation of integrated project healthcare management. In addition, a relationship of eight gains was also presented by the adoption of the model declared by professionals during empirical research, as well as recommendations for replication of the model for healthcare institutions with different levels of maturity. The practical contribution that this study brings is that new projects in the healthcare ecosystem are guided by this model and can produce integrated and complete care services effectively. The social impact generated is that this study helps to overcome the challenges of the healthcare ecosystem and knowledge aligned with the Sustainable Development Objectives (SDGs) recommended by the United Nations, specifically, SDG 3 (health and well-being). This research is aligned with research line 2 (Project Management) linked to the Postgraduate Program in Project Management – PPGP UNINOVE. This dissertation proposal is also aligned with other researchers conducted by your advisor and linked to the project-axis “People Management and Project Management”.